Silagem do terço superior da mandioca com inclusão de milho moído - Andrade, Ida Barbosa de (2021)
The aim of this study was to evaluate the quality and composition of silages from the upper third of cassava (STSM) with the inclusion of 25% of ground corn. Two experiments were carried out, the first used the cultivar Ecu 72, with and without the inclusion of 25% of ground corn. The experimental design was completely randomized, with 4 replications, in split plots in time. The silage loss measurements and microbiological analyzes were evaluated with 7, 15, 30, 45, 60, and 75 days of storage, while pH, temperature, dry, mineral and organic matter were also evaluated in the raw material, in addition to other storage times. The inclusion of corn increased the dry matter of the STSM and this helped to reduce the production of effluents and losses by gases, avoiding the decrease of the nutritional value. In addition, the inclusion of corn improved the fermentative capacity of the silage, as it reduced the buffering capacity, allowing a rapid pH drop. Mesophilic aerobics, clostridium and lactic acid bacteria reduced as storage time increased and silage loss measures were lower in STSM with maize. The second experiment was carried out with two cassava cultivars, Ecu 72 and Baianinha, with and without inclusion of 25% ground corn at different storage times. For pH, temperature, chemical composition and in vitro digestibility evaluations, the experimental design used was completely randomized, with 4 replications, in a 2x2x3 factorial arrangement, with 2 cultivars (Baianinha and Ecu 72); 2 inclusions of 25% ground corn (with and without) and 3 storage times (in natura, 30 and 60 days). The silage loss measurements and the microbiological analyzes of the STSM were not evaluated in natura. The experimental design to evaluate aerobic stability was completely randomized, with four replications, in a 4 x 2 factorial scheme (4 STSM and 2 storage times, 30 and 60 days) with repeated measures in time (7 days of exposure to air). The pH was below 4 at 30 and 60 days of ensiling and the mesophilic aerobics and lactic acid bacteria reduced when the time increased. The inclusion of 25% of corn increased the dry matter (DM) of the silages, reduced the fiber contents, in addition, it increased the carbohydrate contents, improved the digestibility of the material and the fermentative capacity of the silage, as it reduced the buffer capacity allowing a rapid drop in pH and reduced effluent production. Crude protein was higher in cultivar Ecu 72 (115.79 g kg-1), but the highest digestibility of this variable was found in Baianinha (890.13 g kg-1). From the parameters evaluated, it is concluded that the cultivars Baianinha and Ecuador can be used for the production of quality silage, with the inclusion of 25% of ground corn, the composition and digestibility of the silages were high, increasing DM and reducing losses by effluents. Between the times evaluated after ensiling, there was stability of the forage that should be provided to the animals until 72 hours after aeration due to the breakdown of aerobic stability.